Ecological economics and the ecology of economics : essays in criticism - Daly, H.E. (Cheltenham, UK Edward Elgar Publishing, 1999)
The theme throughout the book is about changes in perspective, attitudes and policies required to avoid uneconomic growth- that is, the improvement that results when the environmental and social costs of growth exceed the benefits.
Includes bibliographical references and index
osc 6/9/16
Loans
Keywords: Environmental economics; Ecological economics; Economic growth